Phosphorylation of Caspase-8 (Thr-263) by Ribosomal S6 Kinase 2 (RSK2) Mediates Caspase-8 Ubiquitination and Stability - Peng, Cong (American Society for Biochemistry and Molecular Biology, 2011)
The ribosomal S6 kinase 2 (RSK2) is a member of the p90 ribosomal S6 kinase (p90RSK) family of proteins and plays a critical role in proliferation, cell cycle, and cell transformation. Here, we report that RSK2 phosphorylates caspase-8, and Thr-263 was identified as a novel caspase-8 phosphorylation site. In addition, we showed that EGF induces caspase-8 ubiquitination and degradation through the proteasome pathway, and phosphorylation of Thr-263 is associated with caspase-8 stability. Finally, RSK2 blocks Fas-induced apoptosis through its phosphorylation of caspase-8. These data provide a direct link between RSK2 and caspase-8 and identify a novel molecular mechanism for caspase-8 modulation by RSK2.